Novel Presentation of Sturge–Weber Syndrome in a Boy With a Port-Wine Birthmark - Barbara Anna Folga; Ramzan Shahid (Case Reports in Pediatrics)
Sturge–Weber Syndrome (SWS), also called encephalotrigeminal angiomatosis, is a rare congenital neurological condition classified by the hallmark findings of a port-wine birthmark, leptomeningeal angiomas, and glaucoma. Here, we present a case of a two-year-old patient with a history of a left-sided port-wine birthmark involving the V1-V2 dermatomes who re-presented to the emergency department with focal right-sided seizure-like activity in the setting of a recent head trauma. The patient was admitted for further workup, where video electroencephalography demonstrated the presence of electrographic seizures developing from the left posterior quadrant, with continuous focal slowing over the left hemisphere, and with magnetic resonance venography revealing findings concerning for a pial angiomatosis. This finding, coupled to new-onset seizure-like activity in a patient with a port-wine birthmark, supported a diagnosis of SWS. He was started on an antiepileptic drug regimen with resolution of seizure-like activity while inpatient and his subsequent care was transferred to a specialized clinic designed to manage patients with SWS. Most patients diagnosed with SWS exhibit seizure-like activity, often presenting as infantile spasms, within the first year of life; our patient, on the other hand, began to exhibit focal seizures following a traumatic event and was later found to harbor findings consistent with SWS. Overall, this case highlights the role of a multidisciplinary team in the management of patients with SWS and demonstrates the importance of routine follow-up testing, imaging, and subspecialty care for these patients.